Reducing Energy Efficiency through Virtual Machine Migration - Akilasri, P.S.S; Meenakshi, K (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is one of the important fields in today’s computer world. Many data are being entered in to the cloud network from time to time. As a result, the traffic in the cloud system is also increased. To reduce the energy many algorithms are used. The Virtual Machine Migration algorithm is an algorithm which helps in reducing the energy to a greater deal. The data passed through the cloud through various users are measured and the time efficiency is found and discussed